Pengolahan Pupuk Ramah Lingkungan dari Kotoran Kambing di Desa Jarang Hulu Kabupaten Padang Lawas - Fetra Venny Riza; Josef Hadipramana; Akbar Kurnia Hasibuan (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
One of the potentials owned by Desa Harang Julu, Padang Lawas Regency is livestock, especially goats. However, the excesses caused by farm animals, especially dirt, have a huge impact on health and the environment. In addition, people's habit in processing the manure to be used as compost is less optimal so that agricultural products often do not have maximum impact. Currently, during the Covid 19 pandemic that occurred all over the world, caused an economic recession and decreased income of farming families. With the activities of the training program of making fertilizer from goat manure this gives a new passion impact to farmers. This simple, effective and efficient method of making compost is a new knowledge and experience for farmers in Desa Harang Julu. This fertilizer is made by adding some materials available in nature easily and cheaply, but provides effective results, both in terms of manufacture, process and use and relatively very short use. Thus, this training provides a new hope for farmers to abandon the old way and provide solutions to the outbound economy and have a positive impact on the environment.